The conception of phonological awareness in educational psychology - Gedutienė, Reda (Psichologija, 2010)
Significant research efforts in the field of cognitive, developmental and educational psychology over the past several decades have been focused on the impact of phonological awareness on children’s early literacy development. A substantial body of research evidence from different countries indicates that there is a powerful relationship between preschool phonological awareness and subsequent literacy achievement in alphabetic orthography. There is little research focused on the understanding of phonological awareness in Lithuania, so the aim of this article is to present a theoretical overview of the main areas of the field and to discuss them. First of all, there is a consensus on the definition of phonological awareness, and phonological awareness is broadly defined as a conscious awareness of separate linguistic units in speech and the ability to carry out mental operations on these units of speech. Unfortunately, the relationship between phonological awareness and its many operationalizations is ambiguous, resulting in both theoretical and practical difficulties. Second, there is still no consensus on the structure of phonological awareness. The question is whether the different sets of items intended to measure phonological awareness reflect a single underlying latent ability or several related abilities. Third, research has identified the general sequence of phonological awareness development as universal across languages, and the transparency of a language influences the rate of normal development of phonological awareness. The development of phonological awareness appears to progress from more global phonological characteristics of words to those representing smaller units, i.e. from the syllable level to the phonemic level. A substantial body of research evidence from English indicates that there is a powerful relationship between preschool phonological awareness and subsequent literacy achievements. However, the pattern of findings from research in transparent writing systems with simpler and more consistent letter–sound relationships than English tends to be inconsistent and sometimes contradictory. Some have reported findings more similar to those in English with a strong predictive effect of preschool phonological awareness on early literacy performance. Others have reported that preschool phonological awareness skills are either less important or irrelevant for future literacy attainment.